2017
DOI: 10.1155/2017/1732638
|View full text |Cite
|
Sign up to set email alerts
|

Hip Osteonecrosis Is Associated with Increased Plasma IL-33 Level

Abstract: The recently discovered IL-33 as an IL-1 cytokine family member has been proved to be specifically released from osteonecrotic bones. We aimed to investigate the potential role of IL-33 in the development of osteonecrosis of femoral head (ONFH). Forty patients diagnosed with ONFH and forty age-, sex-, and body mass index- (BMI-) matched healthy subjects were included in this prospective study between March 2016 and September 2016. A commercially available ELISA kit was used to test the level of plasma IL-33. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…In our study, the healthy volunteers ( n = 12) had an average baseline IL33 level of 22.8 pg/mL. This is midrange (5–53 pg/mL) for what has been reported in healthy adult humans [3943]. In injured patients, IL33 levels were the highest in the first 4 hours after presentation, and this was followed by persistent elevations through 7 days in patients that remained in the ICU.…”
Section: Resultssupporting
confidence: 60%
“…In our study, the healthy volunteers ( n = 12) had an average baseline IL33 level of 22.8 pg/mL. This is midrange (5–53 pg/mL) for what has been reported in healthy adult humans [3943]. In injured patients, IL33 levels were the highest in the first 4 hours after presentation, and this was followed by persistent elevations through 7 days in patients that remained in the ICU.…”
Section: Resultssupporting
confidence: 60%
“…Interleukin‐33 (IL‐33), a member of the interleukin‐1 (IL‐1) family, acts as a proinflammatory cytokine via the cell‐surface receptor ST2 . IL‐33 acts on different types of cells, such as osteoblasts, osteoclasts, and osteocytes, and is involved in several acute and chronic inflammatory and autoimmune diseases, such as rheumatoid arthritis and hip osteonecrosis . IL‐33/ST2 signaling has been suggested to be an important bone‐protecting cytokine that decreases bone loss in the femur, with reduced osteoclast formation and activity and stimulation of osteoblastic function .…”
Section: Introductionmentioning
confidence: 99%
“…6 IL-33 acts on different types of cells, such as osteoblasts, osteoclasts, and osteocytes, [7][8][9] and is involved in several acute and chronic inflammatory and autoimmune diseases, 10 such as rheumatoid arthritis 11 and hip osteonecrosis. 12 IL-33/ST2 signaling has been suggested to be an important bone-protecting cytokine that decreases bone loss in the femur, with reduced osteoclast formation and activity 13 and stimulation of osteoblastic function. 9 IL-33 also increases antiosteoclastogenic cytokines, 14 which interfere with the production of receptor activator of nuclear factor κ B ligand (RANKL) and macrophage colony-stimulating factor, 8,9,13,14 thus acting in the bone via indirect pathways.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are not many researches conducted in this branch. In our previous studies, we found that IL-33 was associated with the prognosis of patients with ONFH [17]. This gives us the inspiration to explore the role of immune cells and immunomodulatory cells in ONFH.…”
Section: Introductionmentioning
confidence: 89%